Adaptive protection combined with machine learning for microgrids. Issue 6 (8th March 2019) - Lin, Hengwei; Sun, Kai; Tan, Zheng‐Hua; Liu, Chengxi; Guerrero, Josep M.; Vasquez, Juan C.
Abstract : This paper presents a rule‐based adaptive protection scheme using machine‐learning methodology for microgrids in extensive distribution automation (DA). The uncertain elements in a microgrid are first analysed quantitatively by Pearson correlation coefficients from data mining. Then, a so‐called hybrid artificial neural network and support vector machine (ANN‐SVM) model is proposed for state recognition in microgrids, which utilises the growing massive data streams in smart grids. Based on the state recognition in the algorithm, adaptive reconfigurations can be implemented with enhanced decision‐making to modify the protective settings and the network topology to ensure the reliability of the intelligent operation. The effectiveness of the proposed methods is demonstrated on a microgrid model in Aalborg, Denmark and an IEEE 9 bus model, respectively.